Pengaruh Literasi Keuangan, Sosial Ekonomi, Gaya Hidup, Sosial Media Dan Faktor Lingkungan Terhadap Pengambilan Keputusan Penggunaan Pinjaman Online (Studi Kasus Pada Mahasiswa Di Jember) - Adellia Erika Saputri; Agustin .; Wiwik Fitria Ningsih (GLOBAL SCIENTS PUBLISHER, 2026)
This research was motivated by the increasing use of online lending services among university students, particularly in Jember Regency. Easy access, fast application processes, and massive promotion through social media have made students active users of such services. Unfortunately, many students do not fully understand the risks or assess their financial conditions properly, making them vulnerable to debt traps. This study aims to analyze the influence of financial literacy, socioeconomic status, lifestyle, social media, and environmental factors on students’ decisions to use online loans. The research involved accounting students from five universities in Jember. With a population of 2,974 students, the sample was selected using the Slovin formula and snowball sampling method, resulting in 100 respondents. The data were analyzed using multiple linear regression with the help of SPSS. The results show that, partially, financial literacy and lifestyle significantly influence online loan decisions. Meanwhile, socioeconomic status, social media, and environmental factors have no significant effect. Simultaneously, all five variables have a significant influence on online loan decisions. These findings highlight the importance of improving students’ financial literacy and encouraging a more mindful lifestyle. Educational institutions are expected to strengthen financial education. Future researchers are advised to add variables such as impulsiveness and expand the research area.